상악동 골이식술을 위한 이식재의 부피 측정 - CT를 이용한 환자 대조군 연구 - 김형욱(Hyung-Wook Kim); 이슬기(Seul-Ki Lee); 정재안(Jae-An Chung); 신진업(Jin-Eob Shin); 엄윤섭(Yun-Sub Um); 김기영(Ki-Young Kim); 김종식(Jong-Sik Kim); 송윤정(Yun-Jung Song); 홍순민(Soon-Min Hong); 박준우(Jun-Woo Park) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2007)
(J. Kor. Oral Maxillofac. Surg. 2007;33:511-517)홍 순 민134-010 서울특별시 강동구 길동 445한림대학교 강동성심병원 구강악안면외과Soon-Min HongDept. of OMFS, Kang Dong Sacred Heart Hospital, Hallym Univ.445 Gil-dong, Gangdong-gu, Seoul, 134-010, KoreaTel: 82-2-2224-2333 Fax: 82-2-483-9647E-mail: omfshong@hallym.or.krMEASUREMENT OF MAXILLARY SINUS VOLUME FOR THE PLACEMENT OF GRAFT MATERIAL- A CASE CONTROL STUDY USING CT IMAGEHyung-Wook Kim1, Seul-Ki Lee2, Jae-An Chung3, Jin-Eob Shin3, Yun-Sub Um1, Ki-Young Kim1, Jong-Sik Kim1, Yun-Jung Song3, Soon-Min Hong1, Jun-Woo Park1 Purpose: The aim of this study is to determine whether a difference in the amount of bone graft material is needed between edentulous patients and dentulous patients and to calculate the amount of augmentation for a sinus lift procedure. Methods: 19 patients (20 sinuses) were included to measure maxillary sinus volume. Facial CT scanning was performed using MX 8000 IDT CT devices (Philips, USA). And it was used for IDLvm (The IDL Virtual Machine) 6.0, CT Volume Analyzer Ver 2.3 program to measure maxillary sinus volumes Results: At edentulous patients, volumes (mean±SD) of the inferior portion of the sinuses were 0.56±0.13 cm3 (5mm height), 2.35±0.57 cm3 (10mm height), 4.85±1.10 cm3 (15mm height). At dentulous patients, volumes (mean±SD) of the inferior portion of the sinuses were 0.41±0.18 cm3 (5mm height), 1.76±0.42 cm3 (10mm height), 3.80±0.84 cm3 (15mm height). A significant correlation was found between augmentation height (5mm, 10mm, 15mm) and the calculated sinus volume. (p=0.027, p=0.018, p=0.044) Conclusions: A significant correlation was found between augmentation height (5mm, 10mm, 15mm) and the calculated sinus volume. Detailed preoperative knowledge of sinus lift augmentation volume is helpful in determining the appropriate amount of the bone graft material. KCI Citation Count: 3